Menemukenali Faktor-Faktor Penyebab Kejadian Pernikahan Dini Di Kota Semarang - Santoso, Aprih; Yuantari, Catur (Badan Riset dan Inovasi Daerah Kota Semarang, 2025)
Research objectives: (1) Describe early marriage in Semarang City. (2) Analyze the factors causing early marriage in Semarang City (Having sex for the first time; Education level (women and their partners; Social status/Parents' income; Women's working status; Partner's working status; Level of knowledge and attitudes about early marriage; Role of parents (family parenting patterns); Education at school; Ease of access to information. (3) Analyze the impact of early marriage in Semarang City, especially the incidence of stunting in children. (4) Education for the community in efforts to prevent early marriage. In this study, the method used is a quantitative method to obtain data related to the factors causing early marriage in Semarang City (Having sex for the first time; Education level (women and their partners; Social status/Parents' income; Women's working status; Partner's working status; Level of knowledge and attitudes about early marriage; Role of parents (family parenting patterns); Education at school; Ease of access to information and determine the impact of stunting from early marriage. In addition to quantitative methods, this study also used qualitative methods to dig deeper into information and sources related to handling the reduction of early marriage prevention. As well as information mining by reviewing literature. The population of this study is the Semarang city community who are married and are currently 25 years old. The research sample was taken based on the highest case of early marriage in one of the sub-districts of Semarang City and respondents were taken based on accidental sampling (respondents who were willing to have their data taken. Based on the results of the analysis, in Semarang City the prevalence of stunting reached 21.3% and in 2022 it reached 825 toddlers who experienced stunting from 16 sub-districts. The sub-district with the highest stunting cases was North Semarang reaching 158 toddlers, and the lowest stunting case was Tugu Sub-district reaching 11 toddlers. Based on the results of the study, the age variable for most respondents was 17-20 years old, namely 35 respondents, looking at the first time having sexual intercourse at the age of <19 years, namely 34 respondents and the results of LBW, the majority of children's ages were more than 1 year. From these results, it is possible that they had a secret marriage first, then after being over 19 years old, they registered their marriage legally at the KUA (Office of Religious Affairs). other things that influence the emergence of marriage at a young age are getting pregnant while in school, because the increasingly difficult economic pressures result in frustration, low levels of education, and following trends. In 2020, the trend of early marriage increased due to lack of parental supervision of children which resulted in promiscuity resulting in pregnancy outside of marriage and many of them filed for marriage dispensation to the religious court. There is no relationship between the level of knowledge, attitude, behavior, impact of child marriage with the incidence of stunting, but there is a relationship between BBLR and history of exclusive breastfeeding, parenting patterns and provision of diet with the incidence of stunting